Comparing the diagnostic efficacy of [18F]FDG PET/CT and [18F]FDG PET/MRI in breast cancer recurrence: a systematic review and meta-analysis - Liu, Shiqing; Xie, Yu; Ding, Wei; Ma, Xiaopeng; Li, Zhilin; Zhang, Lei; Zhang, Ya; Ai, Conghui (Frontiers in Medicine, 2025)
PurposeThis meta-analysis evaluates and compares the diagnostic accuracy of [18F]FDG PET/CT and [18F]FDG PET/MRI in detecting breast cancer recurrence.MethodsA search was conducted across PubMed, Web of Science, and Embase databases up to June 10, 2025, to identify studies evaluating the diagnostic performance of [18F]FDG PET/CT and/or [18F]FDG PET/MRI in breast cancer recurrence. Sensitivity and specificity were calculated using the DerSimonian and Laird method with Freeman-Tukey double arcsine transformation. The Quality Assessment for Studies of Diagnostic Accuracy-2 (QUADAS-2) guidelines were employed to perform the quality evaluation.ResultsSeventeen studies involving 1,450 patients were included. At the lesion level, the sensitivity of [18F]FDG PET/CT was 0.97 (95% CI: 0.91–1.00), with a specificity of 0.79 (95% CI: 0.58–0.94). [18F]FDG PET/MRI showed a sensitivity of 0.95 (95% CI: 0.91–0.99) and specificity of 0.87 (95% CI:0.75–0.95). Both modalities demonstrated similar sensitivity (p = 0.71) and specificity (p = 0.66). At the patient level, the sensitivity of [18F]FDG PET/CT was 0.93 (95% CI: 0.88–0.96), with a specificity of 0.87 (95% CI: 0.80–0.93). [18F]FDG PET/MRI showed a sensitivity of 0.99 (95% CI: 0.94–1.00) and specificity of 0.98 (95% CI, 0.90–1.00). Both modalities demonstrated similar sensitivity (p = 0.07) and specificity (p = 0.06).Conclusion[18F]FDG PET/CT and [18F]FDG PET/MRI exhibit comparable sensitivity and specificity in detecting breast cancer recurrence at both the lesion and patient levels. However, high heterogeneity warrants further head-to-head studies to strengthen the evidence and provide more comprehensive insights.